2020
DOI: 10.1111/pbi.13392
|View full text |Cite
|
Sign up to set email alerts
|

Maize BIG GRAIN1 homolog overexpression increases maize grain yield

Abstract: The Zea Mays BIG GRAIN 1 HOMOLOG 1 (ZM-BG1H1) was ectopically expressed in maize. Elite commercial hybrid germplasm was yield tested in diverse field environment locations representing commercial models. Yield was measured in 101 tests across all 4 events, 26 locations over 2 years, for an average yield gain of 355 kg/ha (5.65 bu/ac) above control, with 83% tests broadly showing yield gains (range +2272 kg/ha to À1240 kg/ha), with seven tests gaining more than one metric ton per hectare. Plant and ear height w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…6d). BG1-like genes have been implicated mostly in controlling organ size and yield in rice, Arabidopsis and maize 35,36 . Additional growth-related traits such as plant height, tiller angle, and gravitropism, as well as stress tolerance were affected by down or up regulation of these genes.…”
Section: Selection At Few Key Loci Controls the Main Transitions In Pepper Fruit Evolutionmentioning
confidence: 99%
“…6d). BG1-like genes have been implicated mostly in controlling organ size and yield in rice, Arabidopsis and maize 35,36 . Additional growth-related traits such as plant height, tiller angle, and gravitropism, as well as stress tolerance were affected by down or up regulation of these genes.…”
Section: Selection At Few Key Loci Controls the Main Transitions In Pepper Fruit Evolutionmentioning
confidence: 99%
“…Overexpression of the JcARF19 gene in Jatropha curcas resulted in enlarged seeds in Jatropha curcas ; a similar effect was seen in Arabidopsis [ 45 ]. The auxin transport protein BIG GRAIN 1 can promote grain size in both rice and maize [ 46 , 47 ]. In this study, we also identified transcript alterations associated with the auxin signaling pathway, including auxin response, binding, and transport, which have been reported to be involved in seed development.…”
Section: Discussionmentioning
confidence: 99%
“…These approved traits represent 39 single genes ( Supplementary Table S1 ), and the majority of these genes are related to insect (18) and herbicide tolerance (11). The next generation of GM maize varieties potentially coming to the market comprises events with new insecticidal proteins such as Vpb4Da2, DvSnf7 RNA, and IPDO72Aa to control the population of insects already resistant to Bt ( Schellenberger et al, 2016 ; Moar et al, 2017 ; Yin et al, 2020 ), varieties that exhibit improve grain yield by overexpressing the zmm28 and ZM-BG1H1 genes ( Wu et al, 2019 ; Simmons et al, 2020 ) and varieties that exhibit tolerance to drought stress by overexpressing ARGOS8 ( Shi et al, 2015 ).…”
Section: Development Of Genetically Modified and Edited Varietiesmentioning
confidence: 99%
“…In 2019, genetically modified maize varieties accounted for over 30% of the world’s maize cultivated area ( ISAAA database, 2021 ). The list of the so-called biotech traits currently available is no longer restricted to herbicide and insect resistance; abiotic stress tolerance, high yield, and improved nutritional quality are traits expected to be introduced into the market soon ( Wu et al, 2019 ; Simmons et al, 2020 ; ISAAA database, 2021 ).…”
Section: Introductionmentioning
confidence: 99%